Software reuse methods, models, and costs - Leach, Ronald J. (McGraw-Hill, 1997)
Software reuse offers great cost-saving potential and this book spells out the methods and tools to realize these savings. Covering cost models for reuse, certification for reusable components and reuse-driven requirements engineering, this book helps demystify this area of software development